Reinforcing Life Skill for Preventing and Correcting Amphetamine Addiction among Saiyai-Sampan Group at Bang Bua Thong district, Nonthaburi Province - Leelaphret, Praphut (Journal of Health Science of Thailand, 2018)
Drug addicting has become more complicated based on economic and social changes. For Thailand, even with legal enforcement as well as continuing suppression and rally, current narcotics conditions have not been improved. The most widely used narcotic is amphetamine. Therefore, it is utmost important to reinforce life skill among the risky group so they can avoid drugs temptation. This quasi-experiment was conducted as quasi-experimental research among 100 research participants with the objectives to study effectiveness of reinforcing life skill for preventing and correcting amphetamine addiction among Saiyai-Sampan group at BangBuoThong district, Nonthaburi Province. The samples were divided into an experimental group of 50 participants and 50 participants in a comparison group. The experimental group was subjected to experimentation with group technique in camping and home visit while the control group received common knowledge on amphetamine. Date were collected twice with pre-operation and post-operation through a constructed questionnaire that had been developed based on concepts and elements of life skill, including checking the trace of amphetamine in the urine. Data were analyzed with statistical student’s t-test, paired samples t-test, and pearson’s product moment correlation Findings from post-operation revealed that the experimental group was having better skill in managing emotion and tension, making decision not to take amphetamine, politely refuse taking drugs while maintaining good relationship as well as stop taking drugs at earlier stage, avoid taking amphetamine completely and using more correct methods to prevent drugs addiction and even doing better than the control group with statistical significance. For self-item. it showed higher level at post-operation and better than the control group without statistical significance.